Genomic bases of local adaptation in sheep and goats - Benjelloun B.; Pompanon F.; Ibnelbachyr M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Since their domestication 10.000 years ago followed by a worldwide spread, sheep and goats have accumulated highly valuable adaptive traits allowing them to be raised across highly diverse environments. Besides the current rapid development and wide spread of just a few productive cosmopolitan breeds marked by limited genetic diversity, indigenous populations may keep adaptive traits that would constitute key genomic resources in the context of environmental changes. Within the EU-FP7 funded NextGen project, we applied a landscape genomics framework to identify genes involved in local adaptation. We sequenced the genomes of 160 indigenous sheep and 161 goats representative of the Moroccan-wide diversity in ecology, climate and geographic origin. We detected 39 million variants in sheep and 32 million in goats showing a very weak geographic structure over the country in both species. Using different approaches we identified several sets of loci and genes that likely have a role in local adaptation globally to altitude, slope, sunshine, rainfall, temperature and their variation. The main adaptive pathways were associated with respiration and circulation for the adaptation to altitude. The major genes identified showed different patterns of variation of allele frequencies along environmental gradients. Candidate genes for adaptation to the same environmental variable were generally different between the two species, suggesting different adaptive mechanisms in sheep and goats. However, similar or functionally linked genes responding to the same environmental variable were also found. Results from this study would help in setting up efficient plans of genomic selection based on adaptive traits and be then of major interest for a sustainable management of genetic resources in sheep and goats.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)